Risk factors for early wheezing in preterm infants: a retrospective cohort study - Chen, Xun; Yang, Minjing; Xie, Jun; Huang, Shengzhu; Qin, Xiaolian; Pan, Zhijian; Zhu, Maoling; Zeng, Dingyuan; Huang, Yifeng; Liang, Tao; Liang, Chunmei; Nong, Guangmin (Frontiers in Pediatrics, 2025)
IntroductionThe related factors that cause recurrent wheezing in children are complex, and premature delivery may be one of the reasons. Little is known about early wheezing in preterm infants.MethodsData sourced from 1,616 children born between 2007 and 2013 from 8 hospitals of Guangxi in China. All children were followed by telephone or questionnaire through the sixth year of life. Children were grouped by characters of age: Group A: gestational age (GA ≤ 32 weeks, Group B: 32 weeks < GA < 37 weeks, Group C: 37 weeks ≤ GA < 42 weeks.ResultsThe incidence and the risk factors of early wheezing in preterm infants were analyzed. The incidence of early wheezing: Group A > Group B > Group C. In Group A, the proportion of small-for-gestational-age (SGA) infant was higher in early wheezing group than in normal group (P < 0.05). Male (95% CI: 1.611–4.601) and family history of allergy (95% CI: 1.222–3.411) were the risk factors for early wheezing in Group B.ConclusionsLower gestational age is associated with higher wheezing risk. Preterm infants have higher persistent wheezing incidence than full-term infants. Preterm infants with gestational age <32 weeks have higher transient wheezing incidence than those with gestational age 32–37 weeks or full-term infants. In preterm infants <32 weeks, small for gestational age (SGA) is a potential factor for wheezing. In preterm infants aged 32–37 weeks, male sex, personal allergy history, and family allergy history are potential factors for wheezing, with male sex and family allergy history being significant risk factors.